Statutory Protection of Seasonal Workers under Saudi Labor Law - Sara Essam Atyah,; Amal Mohamed Shalaby Khadragey, (International Journal of Law Research and Studies, 2026)
This study examines and evaluates the regulatory protection system established for workers under seasonal employment contracts within the Saudi Labor Law, utilizing the Hajj sector as a practical model. The research problem stems from the premise that seasonal workers occupy a weaker contractual position due to legal subordination and the brief duration of the season, creating a practical vulnerability that employers may exploit to impose exceptional or arbitrary clauses that disrupt contractual balance. Employing a legal analytical methodology, the study reviews the statutory provisions and ministerial resolutions governing seasonal activities. The study yields a fundamental finding: the parties' autonomy in seasonal contracts is strictly bound by mandatory protective rules that completely invalidate any detraction from workers' rights. Furthermore, this protection is reinforced through rigorous statutory oversight, judicial authority to strike down unfair clauses, and procedural safeguards that secure the worker's rights until the termination of the contractual relationship. Consequently, the study recommends enhancing this protection by automating seasonal contracts via digital platforms, embedding standardized mandatory terms that proactively prevent any violation of the worker's minimum legal guarantees.
Keywords: Seasonal Employment Contract; Regulatory Protection; Exceptional Clauses; Contractual Balance; Saudi Labor Law